2011
DOI: 10.1007/s00464-011-1986-5
|View full text |Cite
|
Sign up to set email alerts
|

Suturing intraabdominal organs: when do we cause tissue damage?

Abstract: BackgroundIt is generally assumed that safety of tissue manipulations during (laparoscopic) surgery is related to the magnitude of force that is exerted on the tissue. To provide trainees with performance feedback about tissue-handling skills, it is essential to define objective criteria for judging the safety of applied forces. To be of clinical relevance, these criteria should relate the applied forces to the risk of tissue damage. This experimental study was conducted to determine which tractive forces duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 13 publications
1
39
0
Order By: Relevance
“…9,10 A maximum allowable peak force of 1.5 N was assigned for both tasks, and the number of times this threshold was breached in each task repetition was regarded as the force error. This value was based on data reported by Rodrigues et al, 14 who determined that macroscopic tissue damage was visible when >1.5 N of tractive force was applied to suture through fresh porcine intestine. Modified scoring metrics (fPLS) were calculated post hoc that imposed additional penalties based on force error.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 A maximum allowable peak force of 1.5 N was assigned for both tasks, and the number of times this threshold was breached in each task repetition was regarded as the force error. This value was based on data reported by Rodrigues et al, 14 who determined that macroscopic tissue damage was visible when >1.5 N of tractive force was applied to suture through fresh porcine intestine. Modified scoring metrics (fPLS) were calculated post hoc that imposed additional penalties based on force error.…”
Section: Methodsmentioning
confidence: 99%
“…The CFF group received continuous feedback about their applied force. Participants in the BFF group were only presented with visual force feedback when their applied force exceeded the threshold of 5.3 N. The threshold was based on a previous study that defined the critical force level that causes tissue damage [19]. Once the visual force feedback was presented, it lingered for 10 s to give the participants the opportunity to notice the feedback and to correct their actions accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…Warning triangles were presented in each corner of the display if extreme force was applied to prevent rupture of the strips. Since the elasticity of the artificial tissue (silicon) is close to that of uterus tissue, the safety thresholds associated with uterus tissue were used in the colour scheme of the force feedback [19].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…In both pre-and post-course assessments in this study, it was observed that all participants exceeded the safety thresholds for tissue damage. Previous research of Horeman et al [31] showed that tissue damage occurs relatively quickly in porcine intestines when pulling a suture. Considering these outcomes and the results of our present study, the repetitive practicing of this surgical technique in a safe simulation environment outside the OR is highly recommended.…”
Section: Portal Force and Torquementioning
confidence: 96%
“…The suture was placed near the ForceSense sensor. Previous studies showed that the maximum needle/suture loading force before the rupture of the large intestine lies between 1 and 3 N [27,30,31]. From the comprehensive data, the mean and max force (Fft) on the intestine were recorded to relate performances to a risk of bowel leaks due to ruptured tissue at the suture site.…”
Section: Parametersmentioning
confidence: 99%